A DNA tool for the identification of heavily exploited Atlantic billfishes - Domingues, Rodrigo R. [UNESP]; Okuda, Gabriel; Bernard, Andrea M.; Amorim, Alberto F.; De Biasi, Juliana; Hilsdorf, Alexandre W. S. (Springer Nature, 2015)
Due to the morphological similarities among species, the International Commission for the Conservation of the Atlantic Tunas has recommended the use of diagnostic molecular tools to allow for robust species-level identifications of the billfishes. In this study, a protocol for the molecular identification of all six Atlantic billfishes was developed utilizing a PCR–RFLP approach, targeting the mitochondrial gene cytochrome c oxidase subunit 1. A survey of 28 restriction endonucleases identified two enzymes (TaqI and HaeIII) that produced species-specific banding patterns sufficient to distinguish species. The protocol was validated against billfishes captured across their Atlantic distributions.
Keywords: COI; Fisheries management; Genetics; PCR–RFLP; Pelagic fish